(Des)caminhos para as cooperativas de catadores de materiais reutilizáveis e recicláveis na grande Aracaju/SE - Oliveira, Fernanda Louisy Ferreira de (2018)
In Brazil, in 2010, Law 12,305 on the National Solid Waste Policy was regulated, which provides guidelines, instruments and targets for the management and management of solid waste. Among these guidelines, it is important to highlight the incentive for social inclusion of recyclable and recyclable waste pickers through waste pickers' cooperatives and their participation in municipal solid waste management, which requires at least twenty members of the cooperative. In this sense, the research aims to analyze the difficulties faced by the cooperatives of recyclable and recyclable material collectors in Greater Aracaju. The method of approach adopted was the inductive and the research procedures included bibliographical research, documentary and field research, through direct observation and interviews, and analysis of information through content analysis. Grande Aracaju has the largest solid waste production in the state of Sergipe, where part of the existing cooperatives can not reach the minimum number of members necessary for its development, even with the support of the public power, since they face problems of a structural, economic, social and operational conditions that compromise sustainability. In order to overcome the difficulties, there is a need for networking among the social actors involved in the management of solid waste in Greater Aracaju so that they can be strengthened collectively.